6t^(-2/3) - t^(-1/3) - 1 = 0

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

solve for t

Nov 30th, 2014

6t^(-2/3) - t^(-1/3) - 1 = 0

6t^(-1/3)*2 - t^(-1/3)-1 =0

let t^(-1/3)=y

6y^2-y-1=0

6y^2-3y+2y-1=0

3y(2y-1)+1(2y-1)=0

(2y-1)(3y+1) =0


2y-1=0  or 3y+1=0

y=1/2 or    y=-1/3

t^(-1/3)=1/2 or t^(-1/3)=-1/3

Taking power -3 both side , we get 

t=(1/2)^(-3)   or t=(-1/3)^(-3)

t=2^(3)  or t= -3^(3)

t=8 or t=-27

I hope, it will really helpful for you.



Nov 30th, 2014

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Nov 30th, 2014
...
Nov 30th, 2014
Oct 23rd, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer